2022
DOI: 10.1038/s41537-022-00219-x
|View full text |Cite
|
Sign up to set email alerts
|

Remote cognitive assessment in severe mental illness: a scoping review

Abstract: Many individuals living with severe mental illness, such as schizophrenia, present cognitive deficits and reasoning biases negatively impacting clinical and functional trajectories. Remote cognitive assessment presents many opportunities for advancing research and treatment but has yet to be widely used in psychiatric populations. We conducted a scoping review of remote cognitive assessment in severe mental illness to provide an overview of available measures and guide best practices. Overall, 34 studies (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 94 publications
(89 reference statements)
0
17
0
Order By: Relevance
“…More recently, studies looking at video neuropsychological assessments found that despite an overall good agreement with the in-person rating of the assessments, there is limited validation and standards for conducting these assessments virtually. [32][33][34] For patients diagnosed with severe mental illness (e.g., eating disorders, psychosis), a systematic review led by Lawes-Wickwar et al in 2018 found that of the 31 articles identified (29 comparative trials), there is inconclusive evidence on the efficacy of virtual mental health care for cognitive rehabilitation, patient education and assessment. 30,35 This is similar to a rapid review conducted on use of virtual modalities of care for treatment of schizophrenia.…”
Section: Findings Efficacy Of Virtual Mental Health Carementioning
confidence: 99%
“…More recently, studies looking at video neuropsychological assessments found that despite an overall good agreement with the in-person rating of the assessments, there is limited validation and standards for conducting these assessments virtually. [32][33][34] For patients diagnosed with severe mental illness (e.g., eating disorders, psychosis), a systematic review led by Lawes-Wickwar et al in 2018 found that of the 31 articles identified (29 comparative trials), there is inconclusive evidence on the efficacy of virtual mental health care for cognitive rehabilitation, patient education and assessment. 30,35 This is similar to a rapid review conducted on use of virtual modalities of care for treatment of schizophrenia.…”
Section: Findings Efficacy Of Virtual Mental Health Carementioning
confidence: 99%
“…Risk profiling of patients based on their clinical history is typically applied in clinical practice by identifying elements such as previous history of suicide attempts, violent attempts, a high genetic loading, and early childhood traumas such as sexual abuse. The evaluation of cognition could support the assessment of the individual suicide risk profile [ 38 , 41 ], and in a dimensional and transdiagnostic framework, exploring the association between TRP metabolism and cognition could be beneficial both in informing new diagnostic-treatment protocols and in improving our understanding of the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Assessing EFs remotely with online tasks continues to grow in popularity, as technological advances can increase speed, efficiency, and sample sizes in data collection (Ahmed et al, 2022; Miller & Barr, 2017). For example, EF tasks are frequently used as part of neuropsychological testing in clinical settings, and some researchers have emphasized the promise of remote EF and cognitive assessments (Bilder & Reise, 2019; Lavigne et al, 2022; Miller & Barr, 2017). Additionally, the COVID-19 pandemic has emphasized the importance of remote psychological assessments and tasks.…”
Section: Technological Advances In Ef Assessmentsmentioning
confidence: 99%